2021
DOI: 10.9734/sajrm/2021/v10i130219
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hookworm (Necator Americanus) and Other Intestinal Parasitic Infection among Primary School Children in Sokoto Metropolis

Abstract: Background: Hookworm is an intestinal parasite of human and is one of the major public health burdens in developing countries, particularly in Sub-Saharan Africa. It is estimated that about 3.5 billion people globally and 450 million people are thought to be ill as a result of such infections, the majority being children. Aims: The study aimed to determine the prevalence of Hookworm and other intestinal parasitic infection among primary school children Study Design: This was a cross-sectional, desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
3
1
0
Order By: Relevance
“…The Lack of significant association in age group from this study could be explained by a shared contaminated environment by the children of all age group. Infection does not significantly associate with the source of water which agreed with the earlier reports by Pandya et al (2017) in India and Mohammed et al (2021) in Sokoto. However, This is contrary to the observation made by Assudani et al (2015) in India and Bala et al (2019) in Sokoto who separately noted the occurrence of hookworm infection was significantly higher in those that having drinking water from open well.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Lack of significant association in age group from this study could be explained by a shared contaminated environment by the children of all age group. Infection does not significantly associate with the source of water which agreed with the earlier reports by Pandya et al (2017) in India and Mohammed et al (2021) in Sokoto. However, This is contrary to the observation made by Assudani et al (2015) in India and Bala et al (2019) in Sokoto who separately noted the occurrence of hookworm infection was significantly higher in those that having drinking water from open well.…”
Section: Discussionsupporting
confidence: 91%
“…The 13.0% overall prevalence of hookworm in this study is however high when compared with findings of Agbo et al (2019) who reported 9.0% of hookworm infection among Pupils of University of Calabar Staff School. The prevalence from this study is also high when compared with 4.5% of hookworm reported by Mohammed et al (2021) among primary school children in Sokoto and 4.9% of hookworm among school children in Samaru, Zaria by Bishop et al (2022).…”
Section: Discussionmentioning
confidence: 51%
“…The Lack of significant association in age group from this study could be explained by a shared contaminated environment by the children of all age group. Infection does not significantly associate with the source of water which agreed with the earlier reports by Pandya et al (2017) [42] in India and Mohammed et al (2021) [28] in Sokoto. However, this is contrary to the observation made by Assudani et al (2015) [8] in India and Bala et al (2019) [10] in Sokoto who separately noted the occurrence of hookworm infection was significantly higher in those that having drinking water from open well.…”
Section: Discussionsupporting
confidence: 90%
“…The 13.0% overall prevalence of hookworm in this study is however high when compared with findings of Agbo et al (2019) [4] who reported 9.0% of hookworm infection among Pupils of University of Calabar Staff School. The prevalence from this study is also high when compared with 4.5% of hookworm reported by Mohammed et al (2021) [28] among primary school children in Sokoto and 4.9% of hookworm among school children in Samaru, Zaria by Bishop et al (2022) [13] . The result is however low when compared with result of study conducted in the North-east Nigeria by Wosu and Onyeabor (2014) who reported 80.9% of hookworm infection and finding in River state by Abah and Irene (2015) [2] who reported 25.0% of the infection among Primary School children.…”
Section: Discussionsupporting
confidence: 38%